Sanciones para legisladores y funcionarios públicos con potestad normativa, por inobservancia a las garantías normativas reconocidas en la Constitución de la República - Tipán Cadena, Luz América (2016)
Starting from the approval and promulgation October of the year 20 2008 of the Constitution of the Republic, they were introduced in her several innovations and reasonable institutions, mainly, of the constitutionalism modern well-known European as Neoconstitucionalismo, among them, the direct and immediate application of the Constitution, the principles of application of the rights, the constitutional supremacy, I enter other; but, the last one of these it is the most outstanding and transformative inside the Ecuadorian juridical classification, since it sends that the Constitution, their postulates and rights recognized in her, they are of obligatory execution and observation for all. And, among those innovations, in the current Constitution we find a whole Title that is the III and that he/she dedicates all their content to the constitutional covenants of title. The same one divides them in: political, normative and jurisdictional, some of which already consisted in the Constitution of 1998. However, the political covenants of title and regulatory schemes are of new it dates, for ende little studied and experts. Particularly, the normative covenants of title mean that through the legislation, of the promulgation of new laws and of reformations to legal bodies already existent, they cannot be restricted neither to harm the fundamental rights recognized in the Constitution. However, this command is not completed neither he/she observes for the National Assembly and the other organs with regulatory powers. In such a virtue, the present work demonstrates like for the neglect and irrespeto to the normative covenants of title that one gives in the country, it is also restricted and viola rights and constitutional covenants of title. I demonstrate it with theoretical investigation and of field